The Correlation Between Self-Efficacy and Motivation on Elderly's Daily Independence - June Cristian G Reguyal (Proceedings Series on Health & Medical Sciences, 2022)
Background: Amongst healthcare workers, nurses are known to struggle with burnout symptoms the most, carrying serious consequences for patients, other healthcare professionals and healthcare organizations. Furthermore, the healthcare sector in the Philippines needs attention, and further studies concerning our Filipino healthcare personnel should be initiated. Objectives: The study was conducted to identify the level of burnout among nurses characterized by the Three Dimensions of Burnout, and the factors influencing burnout characterized by the Six Areas of Work life. Furthermore, the study wanted to determine the relationship between the demographic profile of the respondents, the level of burnout, and the factors influencing burnout. Methods: A quantitative descriptive-correlational study was used, and a total enumeration sampling technique was utilized to select the participants in the study. Data was collected using a three-part survey questionnaire. The conducted research has shown that burnout among the staff nurses of the selected hospitals in Cabanatuan City occurs in all dimensions of this phenomenon (emotional exhaustion, depersonalization, and personal accomplishment). Results: the level of burnout characterized by three dimensions; Emotional Exhaustion, Depersonalization, and Personal Accomplishment. For emotional exhaustion, the majority of the respondents scored 30 and above which implies that 38.0% or 62 respondents have a High Level of Burnout in this dimension. On the other hand, in depersonalization, 63.8% or 104 respondents scored 5 and below which means that they have a Low Level of Burnout in terms of depersonalization. In personal accomplishment, most of the respondents scored 33 and above which implies that the 39.3% of the respondents have a High Level of Burnout characterized by reduced Personal Accomplishment. Conclusion: It was also shown that areas of work life (workload, control, community, reward, fairness, and values) were predictors of occupational burnout among the respondents and were correlated with the dimension of burnout. Community also displayed the highest value of association between the three dimensions of burnout. It is also worth noting that among the profile variables, Salary has shown the most association with the other variables.